Orides Fontela e a contextura poética de Alba: o livro de poesia como objeto poético - Nathan Matos Magalhães (2019)
This dissertation analyzes how a poetry book is organized and how it can be understood as a poetic object. I use the concept of contexture, introduced by the critic Neil Fraistat, to show that Orides Fontela’s books have a specific context. My corpus includes the poet's five books, with a stronger emphasis on "Alba" (1983). The text is divided into three chapters; the first one presents the idea of contexture and the way it works in order to structure the organization of a poetry book; the second presents a study about the poem “Transposição” and its importance for the contexture of Fontela’s books, besides conducting a study around the element “light” as a link between various poems and the books themselves; chapter three analyzes the poems titled “Alba,” as well as the presence of symbols – such as the mirror – the book's themes – such as myth – and the strategies used by the poet to organize the book "Alba" – such as the ideas of construction and deconstruction.